Cognitive and balance functions of astronauts after spaceflight are comparable to those of individuals with bilateral vestibulopathy - Clément, Gilles; Kuldavletova, Olga; Macaulay, Timothy R.; Wood, Scott J.; Navarro Morales, Deborah C.; Toupet, Michel; Hautefort, Charlotte; Van Nechel, Christian; Quarck, Gaëlle; Denise, Pierre (Frontiers in Neurology, 2023)
This study compares the balance control and cognitive responses of subjects with bilateral vestibulopathy (BVP) to those of astronauts immediately after they return from long-duration spaceflight on board the International Space Station. Twenty-eight astronauts and 30 subjects with BVP performed 5 tests using the same procedures: sit-to-stand, walk-and-turn, tandem walk, duration judgment, and reaction time. Compared to the astronauts' preflight responses, the BVP subjects' responses were impaired in all 5 tests. However, the BVP subjects' performance during the walk-and-turn and the tandem walk tests were comparable to the astronauts' performance on the day they returned from space. Also, the BVP subjects' time perception and reaction time were comparable to those of the astronauts during spaceflight.The BVP subjects performed the sit-to-stand test at a level that fell between the astronauts' performance on the day of landing and one day later. These results indicate that the alterations in dynamic balance control, time perception, and reaction time that astronauts experience after spaceflight are likely driven by central vestibular adaptations. Vestibular and somatosensory training in orbit and vestibular rehabilitation after spaceflight could be effective countermeasures for mitigating these postflight performance decrements.